HUBUNGAN FILSAFAT DAN AGAMA MENURUT PANDANGAN IMMANUEL KANT DI ERA MODERN - Dendodi, Dendodi; Radiana, Usman; Simarona, Nuri (Reflektika, 2023)
Religions based on the authority of divine revelation and guidance acknowledge the existence of a metaphysical world which often forms the basis of morals and ethics. Meanwhile, philosophy invites humans to consider and understand the world through reason and rationality and to seek truth with logical reasoning. The two have a relationship that cannot be separated and differentiated because they both have their own entities. In this research, we will discuss the relationship between philosophy and religion according to the views of Immanuel Kant, a great philosopher of the 18th century, based on a view of the modern era. This research was designed using qualitative research methods using a literature study approach , namely collecting reference sources from various literature that are appropriate to the discussion and subject of the study. The conclusion of this study is that according to Kant's view, the essence of religion is in line with universal morality and ethical obligations, not with the dogmatic or ritual aspects of religion. Kant encourages a rational and moral understanding of religion, where humans are expected to act in accordance with their moral obligations without relying completely on religious teachings which is the handle. Thus, Immanuel Kant's views on the relationship between religion and philosophy provide a perspective that respects both domains, while encouraging a more rational and moral approach to religious belief.